Tetrahedral Mesh Improvement Using Moving Mesh Smoothing and Lazy Searching Flips. (2016) - Dassi, Franco; Kamenski, Lennard; Si, Hang
Abstract: We combine the new moving mesh smoothing, based on the integration of an ordinary differential equation coming from a given functional, with the new lazy flip technique, a reversible edge removal algorithm for local mesh quality improvement. These strategies already provide good mesh improvement on themselves, but their combination achieves astonishing results not reported so far. Provided numerical comparison with some publicly available mesh improving software show that we can obtain final tetrahedral meshes with dihedral angles between 40° and 123°.